Critical Temperature-Humidity Index Thresholds for Dry Cows in a Subtropical Climate - Ouellet, Véronique; Toledo, Izabella M.; Dado-Senn, Bethany; Dahl, Geoffrey E.; Laporta, Jimena (Frontiers in Animal Science, 2021)
Effects of heat stress on cows are profound and contribute to lower welfare, productivity, and profitability of the dairy sector. Although dry cows are more thermotolerant than lactating cows due to their non-lactating state, similar environmental thresholds are currently used to estimate the degree of heat strain and cooling requirements. Records of dry cow studies conducted in Gainesville, Florida, USA were pooled and analyzed to determine environmental thresholds at which dry cows exhibit signs of heat stress. Dry-pregnant dams were actively cooled (CL; shade of a barn, fans and soakers, n = 107) or not (HT; shade, n = 111) during the last seven weeks of gestation, concurrent with the dry period. Heat stress environmental indices, including ambient temperature, humidity, and temperature-humidity index (THI), and animal-based indices, including respiration rate (RR), rectal temperature (RT) and dry matter intake (DMI) were recorded in all studies. Correlations were performed between THI and each animal-based indicator. Differences in RR, RT and DMI between treatments were analyzed by regression. Using segmented regression, THI thresholds for significant changes in animal-based indicators of heat stress were estimated. Stronger significant correlations were found between THI and all animal-based indices measured in HT dry cows (-0.22 ≤ r ≤ 0.35) relative to CL dry cows (-0.13 ≤ r ≤ 0.19). Although exposed to similar THI, RT (+0.3°C; P < 0.001) and RR (+23 breaths/min; P < 0.001) were elevated in HT dry cows compared with CL cows whereas DMI (-0.4 kg DM/d; P = 0.003) was reduced. Temperature-humidity index thresholds at which RR and RT began to change were both determined at a THI of 77 in HT dry cows. No significant THI threshold was detected for DMI. At a practical level, our results demonstrate that dry cow RR and RT increased abruptly at a THI of 77 when provided only shade and managed in a subtropical climate. Therefore, in the absence of active cooling, dry cows should be closely monitored when or before THI reaches 77 to avoid further heat-stress related impairments during the dry period and subsequent lactation and to mitigate carry-over effects on the offspring.